Efektivitas Pelaksanaan Pengawasan Metrologi Legal Terhadap Peningkatan Retribusi Daerah di Kota Tanjungpinang - Florianus Yudhi Priyo Amboro; Lily Persyadayani (Journal of Law and Policy Transformation, 2021)
Law Number 23 of 2014 concerning Regional Government has given authority to City Regional Governments to carry out government affairs in the trade sector, namely implementation of calibration, re-analysis, and supervision of legal metrology in sub-affairs in the field of consumer protection.As an autonomous region, the Regional Government of Tanjungpinang City in order to be able to run its government must be supported by sources of regional income, one of which is Regional Retribution which is the original regional income. BDKT calibration, re-analysis and observation services are one of the regional levies collected by the Tanjungpinang City Government. As for the focus of the problems raised in this study are, how is the implementation of legal metrology supervision in Tanjungpinang City, what are the obstacles faced by the Tanjungpinang City Government in implementing legal metrology supervision and collecting curated and recalculated service fees, and what are the solutions to implementation legal metrology supervision in an effort to increase user fees in Tanjungpinang City. From the results of the research conducted, it was found that in order to encourage the implementation of optimal legal metrology supervision, the Regional Government of Tanjungpinang City must meet the factors in the form of the availability of appropriate regulations, as well as the availability of competent human resources in the field of legal metrology so that with the implementation of proper legal metrology supervision, then it will directly provide support to the local government in terms of increasing the amount of local fees that will be used to improve the welfare of the people of Tanjungpinang City